A historical review of nomenclature and high-level classification of praying mantises (Mantodea), including a provisional checklist of the names associated to suprageneric ranks - Roy, Roger (Zootaxa, 2014)
The history of high-level classification of praying mantids is presented. The various historical stages that helped to construct our current knowledge on Mantodea taxonomy and systematic are highlighted through an extensive literature review, from pre-Linnaean times to the present. A provisional checklist of the names associated to suprageneric ranks (family, subfamily and tribe) is also provided, in addition to some remarks on the future efforts that need to be conducted in Mantodea research.